The Degradation of Antracene Compound Using Bacteria Isolated From Paotere Port Waterways - Mirnawati, Mirnawati; La Nafie, Nursiah; Dali, Seniwati (Indonesian Journal of Chemical Research, 2015)
The objectives of this study are (1) Determine the content of antrasena compound in the waste oil at the waterway of Paotere port (2) Determine the characteristics of antrasena degradation bacteria and (3) Determine the percentage of antrasena degradation. In this research an analysis of antrasena compound was conducted with sea water that had been polluted with oil. The next steps were to isolate and characterize the degrading bacteria of antrasena and to analyze the results of antrasena degradation. The results showed that (1) Concentration of the antrasena compound in the waterway of paotere port is 4,8x10-10 ppm. (2) The bacteria can degraded of the antracene is Bacillus cereus (3) There was evidence that Bacillus cereus was able to degrade antracenr compound, the highest degradation percentage is 98,11%, it was achieved on 12 day of incubation